(untitled) (Research, Society and Development, 2022)
The objective of this is to analyze, from the teaching narratives, the “value and strengthen the education professional” axis that was implemented in the State of Goiás during the Political Pact for Education Reform. For that, it makes use of documentary and bibliographic research to apprehend the contemplated objective. In the meantime, there is an apprehension of the context that underlies the educational policy in theory in order to take the reflection of all the aspects that involved this axis, in which since its implementation and until today teachers still experience remnants of this policy that in theory, it was in force between 2011 and 2014. Teachers’ narratives demonstrate that they are devalued, understanding that, according to the current reality of educational institutions, resources, including technological resources, are lacking for the exercise of the profession.